Persistent and changing job strain and risk of coronary heart disease. A population-based cohort study of 1.6 million employees in Denmark - Reiner Rugulies; Elisabeth Framke; Jeppe Karl Sørensen; Annemette Coop Svane-Petersen; Kristina Alexanderson; Jens Peter Bonde; Kristin Farrants; Esben Meulengracht Flachs; Linda L Magnusson Hanson; Solja T Nyberg; Mika Kivimäki; Ida EH Madsen (Nordic Association of Occupational Safety and Health (NOROSH), 2020)
OBJECTIVES: This study aimed to examine the association between job strain and incident coronary heart disease (CHD) in Denmark, while accounting for changes of job strain. METHODS: We included all employees residing in Denmark in 2000, aged 30-59 years with no prevalent CHD (N=1 660 150). We determined exposure to job strain from 1996-2009 using a job exposure matrix (JEM) with annual updates. Follow-up for incident CHD was from 2001-2010 via linkage to health records. We used Cox regression to calculate hazard ratios (HR) and 95% confidence intervals (CI) for the association between job strain and incident CHD. RESULTS: During 16.1 million person-years, we identified 24 159 incident CHD cases (15.0 per 10 000 person-years). After adjustment for covariates, job strain in 2000 predicted onset of CHD during a mean follow-up of 9.71 years (HR 1.10, 95% CI 1.07-1.13). When analyzing changes in job strain from one year to the next and CHD in the subsequent year, persistent job strain (HR 1.07, 95% CI 1.03-1.10), onset of job strain (HR 1.20, 95% CI 1.12-1.29) and removal of strain (HR 1.20, 95% CI 1.12-1.28) were associated with higher CHD incidence compared to persistent no job strain. Associations were similar among men and women. CONCLUSIONS: Job strain is associated with a higher risk of incident CHD in Denmark. As we used a JEM, we can rule out reporting bias. However, under- or overestimation of associations is possible due to non-differential misclassification of job strain and residual confounding by socioeconomic position.